Differential perception of sharp pain in patients with borderline personality disorder - Schloss, Natalie; Shabes, Polina; Kuniss, Sarah; Willis, Franziska; Treede, Rolf-Detlef; Schmahl, Christian; Baumgärtner, Ulf (European journal of pain, 2019)
Background Cutting is the most common method of non-suicidal self-injury (NSSI) to reduce inner tension in patients with Borderline Personality Disorder (BPD). Aim of this study was to compare pain perception induced by an incision and by application of a surrogate model for sharp mechanical pain (a non-invasive “blade”) in BPD. Methods 22 female patients and 20 healthy controls (HC) received a small incision into the volar forearm, a 7s-blade application on the same side, and non-invasive phasic stimuli (pinprick, blade, laser, tactile). Pain intensity as well as affective versus sensory components were assessed. Results Incision was rated similarly by both groups (BPD: 28.6 ± 5.5 vs. HC: 33.9 ± 6.6; mean maximum pain ± SEM; p > 0.8), without significant difference for “7-s-blade” (BPD: 18.1 ± 3.8 vs. HC: 25.3 ± 3.6; mean maximum pain ± SEM; p > 0.17) or between “7-s-blade” and incision (BPD: p > 0.12; HC: p > 0.84). However, patients’ intensity ratings returned significantly faster to baseline after incision (BPD: 38.9 ± 12.6 s vs. HC: 74.52 ± 11.5 s; p < 0.05), and patients evaluated “blade” and incision without any affective and with different sensory descriptors, indicating an altered evaluation of NSSI-like stimulation with qualitative in addition to quantitative differences—especially for the sharp pain component. Conclusions The reduced perception of suprathreshold nociceptive stimuli is based on a missing affective component and specific loss of the perception of “sharpness” as part of the sensory component of pain. The results further demonstrate the usefulness of the “blade” for the perception of sharpness in patients. Significance Patients with Borderline Personality Disorder (BPD) who engage in non-suicidal self-injury (NSSI) report less pain in response to phasic nociceptive stimuli. In comparing an invasive pain stimulus to phasic nociceptive stimuli in BPD patients, the “blade” as non-invasive surrogate model for sharp mechanical pain in psychiatric patients is used. In contrast to healthy volunteers, BPD patients do not report significant affective ratings and specifically display a reduced sensory component for sharpness.
Gesehen am 31.03.2020